2003
DOI: 10.1074/jbc.c300344200
|View full text |Cite
|
Sign up to set email alerts
|

The NMR Structure of the Sensory Domain of the Membranous Two-component Fumarate Sensor (Histidine Protein Kinase) DcuS of Escherichia coli

Abstract: The structure of the water-soluble, periplasmic domain of the fumarate sensor DcuS (DcuS-pd) has been determined by NMR spectroscopy in solution. DcuS is a prototype for a sensory histidine kinase with transmembrane signal transfer. DcuS belongs to the CitA family of sensors that are specific for sensing di-and tricarboxylates. The periplasmic domain is folded autonomously and shows helices at the N and the C terminus, suggesting direct linking or connection to helices in the two transmembrane regions. The str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
121
0
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 101 publications
(129 citation statements)
references
References 23 publications
(15 reference statements)
3
121
0
2
Order By: Relevance
“…It contains a distinct periplasmic sensory domain for C 4 -dicarboxylates that is situated between two transmembrane helices (Golby et al, 1999;Zientz et al, 1998). The structure of the periplasmic domain of DcuS in the liquid state has been solved by NMR (Pappalardo et al, 2003), and the binding site for C 4 -dicarboxylates has been characterized by mutagenesis (Kneuper et al, 2005;Krämer et al, 2007). The second (or C-terminal) transmembrane domain is followed by the cytoplasmic transmitter domain including the histidine kinase domain.…”
Section: Introductionmentioning
confidence: 99%
“…It contains a distinct periplasmic sensory domain for C 4 -dicarboxylates that is situated between two transmembrane helices (Golby et al, 1999;Zientz et al, 1998). The structure of the periplasmic domain of DcuS in the liquid state has been solved by NMR (Pappalardo et al, 2003), and the binding site for C 4 -dicarboxylates has been characterized by mutagenesis (Kneuper et al, 2005;Krämer et al, 2007). The second (or C-terminal) transmembrane domain is followed by the cytoplasmic transmitter domain including the histidine kinase domain.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, like CqsS, many two-component sensors have complicated membrane-spanning domains, which has made structural analyses particularly difficult. For these reasons, analyses of ligandreceptor interactions using structural approaches have been limited to a few histidine kinases with well-defined periplasmic sensing domains and known ligands (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23). Thus, despite intensive effort, it remains unclear how ligand binding affects signaling activity in this important family of receptors.…”
mentioning
confidence: 99%
“…Moreover, genomic sequence analysis revealed that the E. coli four-helix bundle, initially defined in the Tar sensing domain, was not conserved in the chemotaxis receptors of many Grampositive organisms, including the B. subtilis receptors McpA and McpB (20). In addition to these studies, recent structures of the periplasmic binding domains of both the Klebsiella pneumoniae CitA citrate sensor and the E. coli DcuS fumarate sensor showed that an extracellular PAS domain was involved in ligand binding for these two-component sensor kinases (21,22). Finally, the crystal structures of the Vibrio harveyi LuxQ sensor kinase sensing domain (23), the putative sensory box/ GGDEF family protein from Vibrio parahemeolyticus (Protein Data Bank code 2P7J), the Vibrio cholerae DctB sensing domain (25,26), and the sensing domain of the V. cholerae McpN chemoreceptor (Protein Data Bank code 3C8C) revealed a novel architecture for the sensing domains of both bacterial twocomponent sensor kinases and chemoreceptors.…”
mentioning
confidence: 99%